The Students’ Critical Thinking in Acquiring English Speaking - Revi Restu Ayanda; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
Critical thinking is needed to be applied in the English classroom because one of the goals from the implementation of curriculum 2013 is metacognitive intelligence which consists of 4C (Critical Thinking and Problem Solving, Creativity and Innovation, Collaboration, and Communication). However, critical thinking is still rarely used and realized by the students in acquiring English speaking. Stuck in generating ideas is triggered by the low of critical thinking. Sometimes, they know what they want to speak but it cannot be expressed orally. The mistakes anxiety that will be occurred in formulating the sentences is being caused by this problem. To solve those problems, analyzing the students’ critical thinking in acquiring English speaking is conducted on this research. By applying critical thinking, idea blocking will be avoided. This research is conducted by employing the qualitative research method with a thematic analysis approach. After interviewing the informants, The themes of each parameter were found. Brainstorming for interpretation, reluctance for analysis, defense for evaluation, language structure for inference, elaboration for the explanation, and intuition for self-regulation. It could be proven that critical thinking is very needed to be applied in assisting students' minds to formulate the ideas in speaking skills.